Peran Amil Zakat Resmi dalam Meningkatkan Transparasi dan Akuntabilitas Tata Kelola Zakat di Desa Mojopuro - Dina Rustiani Agustina; Fauzun Jamal; Farid Kamal; Adinda Puteri Andris (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the role of officially appointed amil zakat in enhancing transparency and accountability in zakat governance in Mojopuro Village, Wonogiri Regency. Prior to this initiative, Mojopuro had no Zakat Collection Unit (UPZ), resulting in zakat practices that were traditional, undocumented, and lacking institutional oversight. Through a series of mentoring activities and seminars conducted from 8–18 September 2025, capacity-building efforts were directed toward prospective amil zakat, village officials, and religious leaders, focusing on zakat regulations, principles of transparency, and both vertical and horizontal accountability. The implementation methods included material delivery, group discussions, and consultative sessions, which ultimately led to the formal appointment of official amil zakat by the Wonogiri Regency BAZNAS. The findings demonstrate that the presence of official amil significantly improved the structural management of zakat, enhanced participants’ understanding of transparency and accountability, and strengthened coordination among amil, village administrators, and religious figures. These results indicate that village-based institutional mentoring can foster a transformative shift from traditional zakat practices toward professional, transparent, and accountable governance. This study thus offers a community-based empowerment model that can be replicated in other villages to improve zakat distribution effectiveness and build public trust in formal zakat institutions.